2020
DOI: 10.48550/arxiv.2006.05482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coresets for Near-Convex Functions

Murad Tukan,
Alaa Maalouf,
Dan Feldman

Abstract: Coreset is usually a small weighted subset of n input points in R d , that provably approximates their loss function for a given set of queries (models, classifiers, etc.). Coresets become increasingly common in machine learning since existing heuristics or inefficient algorithms may be improved by running them possibly many times on the small coreset that can be maintained for streaming distributed data. Coresets can be obtained by sensitivity (importance) sampling, where its size is proportional to the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…As for the general case of any p ≥ 1, (Tukan, Maalouf, and Feldman 2020) showed that the • p -SVD factorization always exists, and can be obtained using the Löwner ellipsoid. Theorem 2 (Variant of Theorem III (John 2014)).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the general case of any p ≥ 1, (Tukan, Maalouf, and Feldman 2020) showed that the • p -SVD factorization always exists, and can be obtained using the Löwner ellipsoid. Theorem 2 (Variant of Theorem III (John 2014)).…”
Section: Related Workmentioning
confidence: 99%
“…Lemma 7 (Special case of Lemma 15 (Tukan, Maalouf, and Feldman 2020)). Let A ∈ R n×d be a matrix of full rank, p ≥ 1.…”
Section: Computing the Löwner Ellipsoidmentioning
confidence: 99%
“…the Manhattan distance which is the 1 -norm between a point x and its projection, i.e., x − x 1 or sum of differences between the corresponding entries, instead of sum of squared entries, as in the Euclidean distance x − x 2 in this paper. More generally, we may use the p distance x − x p , or even non-distance functions such as M-Estimators that can handle outliers (as in Tukan et al (2020a)) by replacing dist(p, x) with min {dist(p, x), t} where t > 0 is constant (threshold) that makes sure that far away points will not affect the overall sum too much.…”
Section: Generalizations and Extensionsmentioning
confidence: 99%